Transosseous braided-tape and double-row fixations are better than tension band for avulsion-type greater tuberosity fractures. Issue 6 (June 2015) - Brais, Godefroy; Ménard, Jérémie; Mutch, Jennifer; Laflamme, G-Yves; Petit, Yvan; Rouleau, Dominique M.
Abstract: Introduction: The optimal treatment for avulsion-type greater tuberosity fractures is yet to be determined. Three fixation methods are tested: tension band with #2 wire suture (TB), double-row suture bridge with anchors (DR), and simple transosseous fixation with braided tape (BT). Materials and methods: Twenty-four porcine proximal humeri were randomised into three groups: TB, DR and BT. A standardised greater tuberosity (GT) osteotomy was performed at 90° to the humeral diaphysis axis. A mechanical testing machine was used to simulate supraspinatus contraction. The force required to produce 3 mm and 5 mm displacement, as well as complete failure was measured with an axial load cell. Also, three cycles of shoulder flexion/extension with 25 N of supraspinatus contraction were performed. Maximum GT fragment translation and rotation amplitude during one cycle were measured. Results: During supraspinatus contraction, DR and BT groups ( p < 0.05) were superior to TB group for both displacements. The BT technique had the strongest maximal load to failure (BT = 466 N; DR = 386 N; TB = 320 N). For the flexion/extension, DR and BT groups had less displacement and rotation than TB group (anterio-posterior displacement: BT = 2.0 mm, DR = 1.9 mm, TB = 5.8 mm; anterio-posterior angular displacement: BT = 1.4°, DR = 1.0°, TB = 4.8°). No significant difference was observed between DR and BT groups, except for the medio-lateral rotation favouring the DR group. Conclusion: In conclusion, BT and DR are good fixation methods to treat displaced avulsion-type greater tuberosity fractures. They have similar mechanical properties, and are stronger and more stable that the TB construct. Potential advantages of the BT over the DR may be a lower cost and easier surgery. Level of evidence: Basic science study (LEVEL II).